Numerical investigation of clocking effect on a centrifugal pump with inlet guide vanes. Issue 2 (18th April 2016) - Qu, Wanshi; Tan, Lei; Cao, Shuliang; Wang, Yuchuan; Xu, Yun
Abstract : Purpose: – The purpose of this paper is to investigate the clocking effect on a centrifugal pump with inlet guide vanes (IGVs). Design/methodology/approach: – The paper uses a computation fluid dynamics framework to solve the unsteady flows in a centrifugal pump with IGVs. The relative position between the stationary vanes and the stationary volute tongue is defined as the clocking position when IGVs inside the suction pipe rotate along the circumferential direction. Findings: – The results show that clocking positions have little effect on the pump head and efficiency, however their influences are obvious for the pressure fluctuation and flow field in the centrifugal pump. The maximum difference of pressure amplitude at dominant frequency reach up to 28 percent on the monitoring point V8 at different clocking positions under design flow rate. For the large flow rate, the clocking effect on flow field and pressure fluctuation in centrifugal pump is similar to that of design flow rate. However, the clocking effect is nearly negligible at partial flow rate, because there are reverse flows around the tongue tip and obvious vortexes forming and developing in the impeller. Those complex phenomena interacting in the centrifugal pump make the clocking effect less evident. Originality/value: – The numerical investigation reveals the clocking effect on a centrifugal pump with IGVs, which is also valuable for the stable operation and optimal design of centrifugal pumps.